Discovery Learning in Islamic Education for Madrasah Ibtidaiyah Students: Pembelajaran Berbasis Penemuan dalam Pendidikan Islam untuk Siswa Madrasah Ibtidaiyah - Ahnaf, Falihul; Fahyuni, Eni Fariyatul (Adabiyah: Jurnal Pendidikan Islam, 2025)
General background: Islamic religious education in Indonesia has often relied on teacher-centered and traditional methods, which limit student engagement. Specific background: Such approaches tend to cause boredom, passivity, and limited learning outcomes among Madrasah Ibtidaiyah students. Knowledge gap: Few systematic studies have comprehensively reviewed the implementation of innovative strategies, particularly Discovery Learning, within Islamic elementary education. Aims: This article systematically reviews recent studies (2021–2023) to examine how Discovery Learning enhances the effectiveness of Islamic education. Results: The findings reveal that Discovery Learning shifts learning from passive to active, fosters critical thinking, increases motivation, and improves cognitive, affective, and psychomotor outcomes. Novelty: Unlike prior works focusing only on teacher performance, this study highlights the dual role of teachers as facilitators and students as active knowledge seekers within Islamic education. Implications: The study underscores the necessity for educators to adopt Discovery Learning as a transformative pedagogical method, ensuring Islamic education is more participatory, meaningful, and aligned with contemporary learning needs. Highlights: Shifts Islamic education from teacher-centered to student-centered learning. Enhances critical thinking, motivation, and learning outcomes. Provides evidence for Discovery Learning as a transformative method in Madrasah Ibtidaiyah. Keywords: Discovery Learning, Islamic Education, Madrasah Ibtidaiyah, Active Learning, Pedagogy